Microfacies and diagenetic fabric of the Chorgali Formation in Bhuchal Kalan, Kallar Kahar, Salt Range, Pakistan - Jamal, Taha; Azhar, Raja; Haneef, Muhammad; Saboor, Abdus; Ali, Nowrad; Swati, Muhammad Azhar Farooq; Uddin, Zia (Journal of Himalayan Earth Sciences, 2015)
The Chorgali Formation of Eocene age is composed of planar to nodular bedded limestone with shale intercalations, which is exposed in the Bhuchal Kalan, Kallar Kahar of the eastern Salt Range. In this study, a 16.5 m thick stratigraphic section is measured, logged and sampled with a total of 30 samples in two sections (about 1km apart). Four microfacies are recognized from eld and petrographic studies and are: 1) MudWackestone Microfacies, 2) Larger Foraminifera Wacke-Packstone Microfacies, 3) Mixed Bioclastic Wacke-Packstone Microfacies and 4) Shale Lithofacies. These microfacies re-occurred vertically in stratigraphic section. The depositional texture and faunal association suggested that the microfacies represents deposition on a low energy carbonate shelf. The analysis further showed that the Chorgali Formation was also subjected to various diagenetic changes, mainly showing the compaction, aragonite to calcite transformation, tectonically induced fracturing and calcite veins passing from marine diagenesis to meteoric diagenesis through burial diagenesis.